METHODS OF TEACHING FOREIGN LANGUAGES IN THE CONTEXT OF INTERCULTURAL COMMUNICATION - Kuznetsova, Liliya; Germanovna , Natalia; Guseva, Natalia; Nurgaleeva, Tatiana; Shelygov, Aleksandr (Revista Inclusiones, 2020)
The article is devoted to the methodology of teaching foreign languages in the context of intercultural communication. It is established that the condition for students to acquire a sufficiently high level of communicative competence in a relatively short period is the development of social and communicative creativity in the learning process, which is necessary for everyday and professional communication. In this case, this level should allow one to use a foreign language fluently in all types of activities. It is proved that the indicator of the student’s creativity is the ability to solve problems arising in the process of interpersonal communication, participate in role-playing games and find a way out of a difficult, sometimes conflicting, intercultural communication situation. The main task of teaching a foreign language at the present stage is the development and formation of intercultural communicative competence, which at certain stages of language training allows one to use a foreign language both in professional activities and for self-educational purposes.